Factors Related to Drug Adherence in Type 2 Diabetes Mellitus Patients - Dayan Hisni; Erina Dewy Pramesti; Rosmawaty Lubis (Journal of Applied Holistic Nursing Science, 2025)
Background: Untreated Diabetes Mellitus (DM) can cause complications that lead to an increase in the number of deaths and a decrease in quality of life. According to IDF, the death rate in Indonesia for DM patients is 58%. The increase in morbidity and mortality in Indonesia is caused by non-adherence to treatment. There are factors that affect treatment, namely knowledge, self-efficacy, family support and support of health workers. The purpose of this study is to find out what factors are related to medication adherence in patients with Type 2 Diabetes Mellitus at the Sindang Barang Health Center in Bogor. Methods: This study used cross sectional. Sampling was conducted using Purposive Sampling of 88 DM Type 2 respondents who were included in the inclusion criteria. The research instruments were in the form of validated questionnaires, MMAS-8, DKQ-24, HDFSS, DSES, and health worker support which contained 5 questions. The research data was analyzed using the Spearman Rank test. Results: The results showed that there was a correlation between knowledge (p = 0.022 and r = 0.244) and self-efficacy (p = 0.001 and r = 0.342) with medication adherence. However, there was no correlation between family support (p = 0.061 and r = 0.201) and health care worker support (p = 0.078 and r = 0.189) with medication adherence. Conclusion: There is a correlation between the patient's knowledge and self-efficacy and medication adherence. Therefore, it is necessary to increase education and self-efficacy to increase patient compliance in undergoing treatment.